(untitled) (Journal of Laboratory Animal Science, 2025)
The Journal of Laboratory Animal Science (JLAS) functions as the official publication for the Laboratory Animal Scientists Association of India. Founded in 2004, JLAS seeks to promote discussions on experimental knowledge and to further the science and technology linked to laboratory animal sciences. Since its first issue in 2018, Journal of Laboratory Animal Science has released 61 research articles. In the year 2024, JLAS selected ACS Publisher and responsible for publishing articles for JLAS. I am delighted to report that the submission rate has increased, in contrast, the average time to reach a final decision is decreasing, thanks to the adoption of online submission and review processes by ACS publisher. All articles are now assigned a DOI, and they are cross-referenced and indexed in UGC Care, Index Copernicus, and other indexing systems. We expect to achieve Scopus indexing shortly, which will facil itate indexing in PubMed. Thanks to reviewers and members of the Editorial Board to review the articles in time. JLAS is carving out a unique niche among service-oriented journals, with its main objective being the advancement of knowledge and the encouragement of ethical practices in the care, use, and management of laboratory animals in bio medical and veterinary research environments. By serving as a conduit for innovative research, JLAS aims to improve laboratory animal welfare, ensure compliance with regulations, and promote scientific innovation. As a result, JLAS covers a broad spectrum of application areas and methodologies related to laboratory animals, and its impact seems to be consistently expanding. I am delighted to share the advancements made by Laboratory Animals through the execution of several outreach initiatives, which encompass conferences, seminars, workshops, and innovations carried out by various members of LASA.